Middle-Income Trap: A Literature Review - Fatih Karasaç; Ahmet Burçin Yereli; Fatih Akbayır (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The main aim of this paper is to analyze the theoretical and empirical dimensions of a relatively new phenomenon in economics literature, namely “Middle-Income Trap”, which was firstly discussed by Gill and Kharas (2007). In general, this phenomenon is related to middle-income economies which have several difficulties in exceeding a certain level of per capita income. In this regard, most of the studies focus on developing countries and theoretically scrutinize the key factors behind this vicious circle. Accordingly, these studies also offer policy implications associated with issues like productivity, quality of education and technological progress. On the empirical side, most of the studies draw more attention to Thailand, Mexico, Brazil and Malaysia as these countries desperately struggle to escape from this trap.